1989
DOI: 10.1111/j.1349-7006.1989.tb01709.x
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Cellular Molecules in Human Cells Detected by Monoclonal Antibodies Reactive with c‐myc Proteins Produced in Escherichia coli

Abstract: Six clones of monoclonal antibodies, MYC‐1 to ‐6, were prepared by using two kinds of truncated c‐myc proteins, p23 and p42, produced in Escherichia coli as immunogens. Analysis with enzyme‐linked immunosorbent assays and immunoblotting assays with peptides produced in Escherichia coli showed that 5 clones of monoclonal antibodies, MYC‐1 to ‐4 and ‐6, were reactive with c‐myc protein encoded by exon 2. The remaining one clone, MYC‐5, was reactive with the portion of c‐myc protein encoded by exon 3. All monoclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1991
1991
1994
1994

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…MYC-l was detected not only in tumor cells but also in stromal cells. MYC-l is a protein for the identification of the 58-and 60-kDa protein expressed by the human c-myc gene [15], In our western blotting study, single bands to molec ular weight 60 kDa were recognized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MYC-l was detected not only in tumor cells but also in stromal cells. MYC-l is a protein for the identification of the 58-and 60-kDa protein expressed by the human c-myc gene [15], In our western blotting study, single bands to molec ular weight 60 kDa were recognized.…”
Section: Discussionmentioning
confidence: 99%
“…Suzuki et al [14] showed, however, that p62 immunoreac tivity was detected in the cytoplasm regardless of the fixa tion. We used antisera (MYC-1) to two laids of truncated human c-myc protein in Escherichia coli as produced by Naoeet al [15]. The M YC-I used in this study was detect ed in the cytoplasm of tumor cells, but a few cells showed positively stained nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…MYC-I reacts specifically with c-myc protein encoded by exon 2. MYC-1 was confirmed to detect bands at the levels of 58 and 60 kDa, that were detectable in nuclear extracts of HL-60 and COLO320, both of which amplified c-myc genes [13].…”
Section: Monoclonal Antibodymentioning
confidence: 93%
“…In our previous report, the staining of c-myc gene product with monoclonal antibody was predominantly cytoplasmic despite the known nuclear location of p62c-myc from im munochemical studies [14][15][16][17][18]. Naoe et al [13] report ed that MYC-1 detected bands at the levels of 58 and 60 kDa, that were detectable in nuclear extracts of HL-60 and COLO320, both of which have amplified c-myc genes, and also in the extract of RmycYI which is the c-myc transfectant into 3YI rat cells. In the present study, however, staining with MYC-1 was predominantly cytoplasmic.…”
Section: Discussionmentioning
confidence: 99%
“…Frozen tissues were sectioned at 6 pm thickness and fixed in 6% neutral formalin. Monoclonal mouse antibody against C-MYC protein, which was produced in Escherichia coli, MYC-1 (IgG,) (Naoe et al, 1989) was kindly provided by Dr. Shiku (Nagasaki University, Japan). After application of biotinylated horse anti-mouse immunoglobulin, staining was carried out by Vectorstain ABC kit (Vector, Burlingame, CA).…”
Section: Immunohistochemical Detection Of C-myc Proteinmentioning
confidence: 99%